Modelling Changes in the Cognitive Processing of Grammar in Implicit and Explicit Learning Conditions: Insights From an Eye‐Tracking Study. Issue 3 (2nd May 2018) - Indrarathne, Bimali; Ratajczak, Michael; Kormos, Judit
Abstract: This study used eye‐tracking to examine changes in how second language (L2) learners process target grammatical exemplars in written L2 input in implicit and explicit instructional conditions and how these changes relate to learning gains. In three separate sessions, 77 L2 learners of English read a story containing seven examples of a grammatical construction. The results of a growth curve analysis indicated significant main effects for the instructional condition and test sessions on total fixation duration and a significant interaction between these two variables. There was minimal attentional processing and no improvement in processing efficiency of the target construction in the unenhanced condition. Learners' attentional processing in the textually enhanced conditions decreased and, by the end of the experiment, they engaged in establishing and fine tuning form–meaning links. In the two explicit instructional conditions, participants' attention decreased over time and form–meaning representations of the target structure were strengthened. Open Practices: This article has been awarded an Open Materials badge. All materials are publicly accessible via the IRIS Repository athttps://www.iris-database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .